Quality control and GMP synthesis of 68Ga-prostate-specific membrane antigen-11 for detection of low- and high-grade prostate cancer - Assadi, Majid; Dadgar, Habibollah (World Journal of Nuclear Medicine, 2020)
Prostate-specific membrane antigen (PSMA) labeled with 68Ga routinely used with higher sensibility and specificity than other radiotracers for detection of low and high grades of prostate cancer using positron emission tomography (PET)-computed tomography. 68Ge/68Ga generators are generally used with automated modules for the syntheses of 68Ga radiopharmaceuticals. The aim of the current study is to describe the procedures for labeling PSMA with radiotracers and their standard QC tests. The automated synthesis method for 68Ga-PSMA-11 was taken and set of a quality control based on chromatographic and spectrometric methods used to determine radiochemical and radionuclide purity of the radiolabeled compound. Meanwhile, high-performance liquid chromatography and rainbow trail Lutheran camp are the best choices after stability tests for assessment of radiochemical purity at the optimized conditions. The clinical utility of the synthesized radiopharmaceuticals was ascertained by performing PET scans in human patients.
Keywords: Computed tomography; positron emission tomography; prostate cancer; prostate-specific membrane antigen-11; quality control